The effect of technological innovation on international trade: a nonlinear approach - Laura Márquez-Ramos; Inmaculada Martínez-Zarzoso (Kiel Institute for the World Economy (IfW), 2009)
This paper focuses on the relationship between technological innovation and international trade. In particular, the effect of technological achievement on exports is studied. In order to measure technological innovation, the technological achievement index (TAI) is used, thus providing a summary of a society's technological achievements and allowing countries to be classified into four groups according to their level of technological innovation: Leaders, Potential Leaders, Dynamic Adopters and Marginalised. The effect of technological variables on sectoral exports is analysed using a gravity model of trade. The existence of a possible non-linear relationship is also investigated, since the effect of improved technological innovation on trade could vary according to the technological achievement in countries. Results show the expected positive effect of technological innovation on export performance and the existence of non-linearities is confirmed. A 'U-shaped' relationship is found between exports and creation of technology and between exports and diffusion of old innovations, whereas an inverted-'U-shaped' relationship is found between exports and diffusion of recent innovations and between exports and human skills.
Keywords: 330; Technological innovation; sectoral exports; gravity model; panel data; non-linearities; Innovation; Technischer Fortschritt; Export; Innovationsdiffusion; Komparativer Kostenvorteil; Gravitationsmodell; Welt